Austria - Korea : International Exchange Project of Contemporary Art 1993. - Korean Institute of Industrial Design & Packaging, Seoul (Wien : Kulturverein Aus-Art, 1993)
Kim, Kwang-Hyun ; Kim, Keun-Tai ; Kim, Sun ; Kim, Yun-Hoon ; Kim, Hae-Dong ; Park, Byung-Choon ; Baik, Kum-Nam ; Sun, Jong-Sun ; Shin, Ho-Chul ; Shim, Jai-Ku ; An, Chi-In ; Yeom, Moon-Sun ; Lee, Keun-Myung ; Lee, Doo-Seop ; Lee, Jai-Min ; Lee, Jung-Hoon ; etc.
Austria - Korea : International Exchange Project of Contemporary Art, Korean Institute of Industrial Design & Packaging, Seoul/Korea, 23-28 June 1993 ; Exhibition in the Pavilion at the Traisen, St. Pölten/Austria, 2-17 September 1993
boek
Keywords: Korea; Oostenrijk